Analysis of Writing Practice Frequency and Prose Writing Ability at Vocational High School - Barus, Erna Wati (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The ability to write descriptive prose is influenced by a person's linguistic insights and language skills, which can be actualized through regular writing practice. This quantitative research with a correlational approach aims to examine the relationship between the frequency of writing practice and the ability to write descriptive prose of grade X students of SMK Immanuel Kabanjahe, 2023 school year. Data was taken from 45 students in grades X-2 as a sample representing a population of 135 students. Data collection techniques are done through interviews, questionnaires, and essay tests. Data analysis uses the Product Moment correlation statistical technique. The results showed a significant relationship between the frequency of writing practice and the ability to write descriptive prose with an R_value of 0.871, which was higher than the r-value in the table of 0.294. It is proven that the frequency of writing practice plays an important role in improving students' descriptive prose writing skills.